The Role Of Fiscal Policy In Reducing Income Inequality In Emerging Economies - Muh Habibulloh; Himad Ali (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study examines the effectiveness of fiscal policy in reducing income inequality across five Southeast Asian countries: Indonesia, Malaysia, the Philippines, Thailand, and Vietnam. Using a comparative approach, the research analyzes the trends in Gini coefficients alongside fiscal indicators such as tax-to-GDP ratios, social spending as a percentage of GDP, and the progressivity of transfer programs from 2010 to 2022. The findings indicate substantial variation in fiscal performance and redistributive outcomes. Vietnam and Thailand have demonstrated notable success in reducing inequality, supported by progressive tax systems and sustained investments in health and education. In contrast, Malaysia, despite relatively high social spending, showed limited redistribution due to a less progressive tax structure. Indonesia and the Philippines have implemented targeted transfer programs, yet structural weaknesses in tax collection and program implementation have limited their effectiveness. The analysis highlights that fiscal policy effectiveness depends not only on the amount of resources mobilized but also on how equitably and efficiently those resources are allocated. The study concludes that adequate fiscal capacity, political commitment, and institutional efficiency are essential to enhancing the redistributive impact of fiscal policy. The findings provide valuable insights for policymakers seeking to design inclusive and equitable fiscal strategies in emerging economies.